Description of three new species of frogs in the genus Pristimantis (Anura: Terrarana: Strabomantidae) of the cloud forests in the Metropolitan District of Quito, Ecuador - Mario H. Yánez-Muñoz (ACI Avances en Ciencias e Ingenierías, 2010)
We describe three new species of frogs Pristimantis from the Distrito Metropolitano de Quito based on material collected by expedition of the Museo Ecuatoriano de Ciencias Naturales. The new species are assigned to the P unistrigatus, P devillei and P myersi species-groups, and can be distinguished easily from similar species by external morphology and distinctive coloration patterns. The three new species were discovered in the extensive and unexplored forests on the northern and southwestern slopes of the Pichincha volcano, which preserves an endemic and still poorly-known fauna.